Clinicoradiographic evaluation of hyaluronan-nano hydroxyapatite composite graft in the management of periodontal infrabony defects - Eeshita Bhowmik; Deepika Pawar Chandrashekara Rao (Wolters Kluwer Medknow Publications, 2021)
Background: Hyaluronan is a naturally occurring polysaccharide in the extracellular matrix of the connective tissue. It imparts antibacterial and osteogenic properties to the nano hydroxyapatite bone graft (NHA). Aim: This study aims to evaluate the efficacy of hyaluronan-NHA (H-NHA) composite in the treatment of infrabony defects in chronic periodontitis patients. Materials and Methods: Eight systemically healthy chronic periodontitis patients with 32 graftable sites were included in the study. After flap reflection and debridement, the defect sites in the test quadrant were filled with H-NHA graft and those in the control quadrant were filled with NHA graft alone. Clinical parameters such as probing pocket depth (PPD) and clinical attachment level (CAL) were assessed at baseline and 3, 6, 9, and 12 months; bone probing depth (BPD) and radiographic parameters such as amount and percentage of defect depth reduction (DDR, PDDR) and change in alveolar crest level (ALR) were assessed at baseline and 6 and 12 months. Statistical Analysis Used: Descriptive statistics, one-way analysis of variance, and Student's t-test were used for statistical analysis. Results: At the end of 12 months, H-NHA group showed a greater reduction in PPD (5.06 ± 0.582 mm), BPD (4.22 ± 0.371 mm), and gain in CAL (4.00 ± 0.421 mm) as compared to the NHA group (3.21 ± 0.648 mm, 3.21 ± 0.047 mm, and 2.86 ± 0.127 mm, respectively). In addition, DDR, PDDR, and ALR were better in H-NHA group (1.92 ± 0.647 mm 48.22 ± 31.561 mm, and 1.22 ± 0.808 mm, respectively) as compared to the NHA group (1.14 ± 0.602 mm, 20.14 ± 25.349 mm, and 0.89 ± 0.626 mm, respectively). Statistically significant improvements in all the parameters were seen in the test sites when compared to control sites at 12 months. Conclusion: H-NHA composite graft can be considered a promising periodontal regenerative material.